Pretreatment with pentoxifylline attenuates lung injury induced by intestinal ischemia/reperfusion in rats - Marqui, Carlos Eduardo [UNIFESP] (2011)
PURPOSE: To investigate the protective effect of pentoxifylline against the lung injury observed after intestinal ischemia (I) followed by a period of reperfusion (R). METHODS: Twenty-eight male Wistar rats were equally divided into 4 experimental groups and operated under ketamine-xylazine anesthesia. (1) Sham: falsely-operated animals; (2) SS+IR: intestinal ischemia was accomplished by clipping the superior mesenteric artery during 60 minutes, with an administration of a standard volume of saline solution (SS) 5 min before the end of the ischemia period; the clip was then releases or a 120-min period of reperfusion; (3) I+PTX+R: ischemia as above, PTX was administered (25 mg/kg) and the gut reperfused as above; (4) PTX+I+PTX+R: Five minutes before arterial occlusion PTX was administered; the superior mesenteric artery was then clipped for 60 minutes. After 55-min ischemia, an additional dosis of PTX was administered; the clip was removed for reperfusion as above. At the 60th min of reperfusion a third dosis of PTX was administered. RESULTS: PTX markedly attenuated lung injury as manifested by significant decreases (all P<0.001 as compared with the SS+IR group) of pulmonary wet/dry tissue weight ratio, total protein content, myeloperoxidase activity and tumor necrosis factor-alpha. Moreover, it was apparent that in the group PTX+I+PTX+R the improvements have been even more significant. CONCLUSION: PTX exerted a protective effect on the lung from the injuries caused by intestinal ischemia/reperfusion.